Constructed Wetland-Based Wastewater Management Model for Slum Settlements in 9-10 Ulu Urban Village, Jakabaring District, Palembang City - Elizabet Matolisi; Alimin (Bioscientist : Jurnal Ilmiah Biologi, 2026)
This study aimed to assess water quality based on physicochemical and microbiological parameters, identify the dominant social factors influencing pollution, and evaluate the performance of a Constructed Wetlands (CW) model as a domestic wastewater treatment solution. Water sampling was conducted at three stations along the Aur River in accordance with Indonesian National Standards (SNI). Dominant factor analysis was performed using linear and logistic regression with SPSS version 24, while CW performance was evaluated using independent t-tests in horizontal and vertical flow systems planted with three types of vegetation: water spinach, water hyacinth, and water lily. The results showed that the highest total coliform concentration was recorded at the downstream station, reaching 9 × 10⁶ MPN/100 mL. Septic tank ownership was identified as the most dominant variable associated with total coliform concentration (OR = 9.470). All water quality parameters decreased significantly after CW intervention (p = 0.000), with removal efficiencies of 91.43% for BOD, 86.41% for COD, 94.24% for ammonia, and up to 96.05% for total coliform. No significant difference in treatment performance was observed between the horizontal and vertical configurations, indicating that CW design selection may be guided by cost considerations and site-specific field conditions.